2021
DOI: 10.3390/rs13050977
|View full text |Cite
|
Sign up to set email alerts
|

Yield Prediction in Soybean Crop Grown under Different Levels of Water Availability Using Reflectance Spectroscopy and Partial Least Squares Regression

Abstract: Soybean grain yield has regularly been impaired by drought periods, and the future climatic scenarios for soybean production might drastically impact yields worldwide. In this context, the knowledge of soybean yield is extremely important to subsidize government and corporative decisions over technical issues. This paper aimed to predict grain yield in soybean crop grown under different levels of water availability using reflectance spectroscopy and partial least square regression (PLSR). Field experiments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 71 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…PLSR is a nonparametric regression analysis method based on factor analysis, which is highly suitable for modeling under the condition of a small number of high-dimensional samples. Many studies have shown that it has excellent performance in the spectral estimation of soil material content [44][45][46]. Table 3 indicates that the optimal characteristic bands of soil petroleum hydrocarbon hyperspectral imaging selected using GARF can extract most of the important information in only a small amount of bands: CR-GARF had the best effect, in which 82% of the important information was contained in 17 characteristic bands (420, 1220, 1230, 1720, 1760, 1780, 1790, 1830, 2190, 2210, 2260, 2300, 2310, 2340, 2350, 2360, 2390 nm, only 8.37% of entire bands).…”
Section: Estimation Accuracies Of Soil Petroleum Hydrocarbon Contentmentioning
confidence: 99%
“…PLSR is a nonparametric regression analysis method based on factor analysis, which is highly suitable for modeling under the condition of a small number of high-dimensional samples. Many studies have shown that it has excellent performance in the spectral estimation of soil material content [44][45][46]. Table 3 indicates that the optimal characteristic bands of soil petroleum hydrocarbon hyperspectral imaging selected using GARF can extract most of the important information in only a small amount of bands: CR-GARF had the best effect, in which 82% of the important information was contained in 17 characteristic bands (420, 1220, 1230, 1720, 1760, 1780, 1790, 1830, 2190, 2210, 2260, 2300, 2310, 2340, 2350, 2360, 2390 nm, only 8.37% of entire bands).…”
Section: Estimation Accuracies Of Soil Petroleum Hydrocarbon Contentmentioning
confidence: 99%
“…As a result, the spectral data were transformed into a linear model composed of waveband scaling coefficients [41]. PLSR (p ≤ 0.05) was performed by the Unscrambler ® (CAMO Software, Oslo, Norway) based on the optimal number of latent variable, as indicated by the lowest value of root mean square error (RMSE) through the leave-oneout cross-validation method, the highest coefficient of determination (R 2 ) of multivariate regression, and the value of systematic error (BIAS) close to zero [42]. The accuracy of the PLSR models was assessed with the Pearson coefficient (r) and the coefficient of determination (R 2 ) from the linear regression between observed and predicted LWC during the leave-one-out cross-validation procedure.…”
Section: Partial Least Squares Regression (Plsr) For Lwc Monitoringmentioning
confidence: 99%
“…In the 2017-2018, 2018-2019, and 2019-2020 crop seasons, Brazil consolidated its status as the world's largest producer, with productions of 123.4, 119.7, and 126.0 million tons (World Agricultural Production-USDA 2022). However, global and national production is constantly threatened by various biotic and abiotic factors [1][2][3][4][5][6][7][8], which can compromise grain yield and producer profitability.…”
Section: Introductionmentioning
confidence: 99%